New Straits Times, 13 September 2007 - Sonia Raachandran (The New Straits Times Press (M) Bhd, 2007)
Kuala Lumpur's special charm has lured many over the centuries in search of wealth and success. the city has seen a phenomenal transformation from a rural backwater to a cosmopolitan centre equal to the best in the world.